Does Economic Growth, Government Spending, Open Unemployment, and Consumption Patterns Affect the Human Development Index Islamic and Human Development Index? - M. Iriansyah Harahap; Asmuni; Sudirman Suparmin (LPPM, Universitas Islam Syarifuddin Lumajang, 2024)
This concept cannot yet be a universal measure of human development. The Islamic human development index (I-HDI) is here to offer a concept for measuring human development based on maqāṣid al-sharī‘ah. The research aims to analyze economic growth in mediating the influence of government spending on the education, health, and social sectors, open unemployment, and consumption patterns on I-HDI and HDI. The research results of government spending on the education, health, and social sectors as well as consumption patterns is positive and significant, while economic growth and the Open Unemployment Rate (TPT) have a positive but not significant effect on I-HDI. Meanwhile, government spending on the health sector, social sector, and consumption patterns have a positive and significant effect, government spending on the education sector has a negative and insignificant effect, and economic growth and TPT have a positive and insignificant effect on HDI. The magnitude of the direct influence on IHDI is 53.04 percent and on HDI is 59.71 percent. Economic growth as an intervening variable is unable to mediate the influence of government spending on the education sector, government spending on the health sector, government spending on the social sector, TPT, and consumption on I-HDI and HDI.